2011
DOI: 10.1039/c1nr10491h
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling time in a near-field approach to scanning probe microscopy

Abstract: Microwave microscopy has recently attracted intensive effort, owing to its capability to provide quantitative information about the local composition and the electromagnetic response of a sample. Nonetheless, the interpretation of microwave images remains a challenge as the electromagnetic waves interact with the sample and the surrounding in a multitude of ways following different paths: microwave images are a convolution of all contributions. In this work we show that examining the time evolution of the elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…Unlike destructive imaging techniques such as focused ion beam milling combined with scanning electron microscopy ( 22 ), transmission electron microscopy (TEM) ( 23 ), and secondary ion mass spectrometry (SIMS) ( 24 ), SMM experiments can be performed with virtually no sample modification, in an ambient environment, using a standard atomic force microscope (AFM) ( 25 ) or STM ( 26 ) combined with a vector network analyzer (VNA) ( 27 ) or custom-made electronics ( 28 ). Typically, resonators ( 29 ) or matching circuits ( 28 ), as well as simpler direct connections ( 30 , 31 ), are used to sense the minute electrical changes that come from the SMM probe. Recently, it has been shown that SMM is capable of visualizing buried conducting structures ( 20 , 21 , 32 ) and differently doped bulk regions buried below an insulating layer ( 33 ).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike destructive imaging techniques such as focused ion beam milling combined with scanning electron microscopy ( 22 ), transmission electron microscopy (TEM) ( 23 ), and secondary ion mass spectrometry (SIMS) ( 24 ), SMM experiments can be performed with virtually no sample modification, in an ambient environment, using a standard atomic force microscope (AFM) ( 25 ) or STM ( 26 ) combined with a vector network analyzer (VNA) ( 27 ) or custom-made electronics ( 28 ). Typically, resonators ( 29 ) or matching circuits ( 28 ), as well as simpler direct connections ( 30 , 31 ), are used to sense the minute electrical changes that come from the SMM probe. Recently, it has been shown that SMM is capable of visualizing buried conducting structures ( 20 , 21 , 32 ) and differently doped bulk regions buried below an insulating layer ( 33 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, their use do not eliminates topographic cross-talk effects. Finally, the approach proposed by Farina et al, 42 based in analysing the SMM response in time rather than in frequency, while allowing to cancel the stray, it doesn't solve the problem of the local signal changes due to the tip vertical movement, which still occurs between the tip apex and the sample. In this scope, our method represents a valid option to resolve these issues, which is even applicable with non-optimal conventional, and widely available, conductive AFM probes.…”
Section: Discussionmentioning
confidence: 99%
“…To end up, we would like to strees that the problematics of disantangling topographic from electric permittivity contributions in AFM-SMM capacitance images can not be solved by other approaches proposed to date, which involve the use of alternative imaging modes, such as constant height imaging, 41 the use of special tip configurations, such as shielded probes 6,8 and open ended coaxial probes, 3 or the use of specific post-processing algorithms, such as time domain. 42 For instance, constant height imaging by definition contains no topographic cross-talk effects, since the probe-substrate distance is not varied. However, in non-planar samples it provides optimal signal to noise ratio only on the tallest parts of the sample, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Their work indicated that AFM can be an effective tool for gene/molecule delivery. Furthermore, nowadays, with the development of AFM-based and microwave microscope technology, the THP1 cells (Oh et al 2011) Yucca filamentosa's epidermal cells (Park et al 2005) C2C12 cells (Farina et al 2011(Farina et al , 2012, cancerous breast cells (Tabib-Azar and Wang 2004) have been imaged by scanning microwave microscopy.…”
Section: Introductionmentioning
confidence: 99%